Do differences in the scale of irrigation projects generate different impacts on poverty and production? - Dillon, Andrew (International Food Policy Research Institute, 2010)
This paper investigates differences in household production and consumption among small- and large-scale irrigators to assess whether the scale of an irrigation project increases household welfare in Mali. Much of the evidence of the impact of irrigation does not use counterfactual analysis to estimate such impact or distinguish between the scale of the irrigation projects to be evaluated. In the dataset collected by the author, both a large-scale irrigation project and small-scale projects are used to construct counterfactual groups. Propensity score matching is used to estimate the average treatment effect on the treated for small and large irrigators relative to nonirrigators on agricultural production, agricultural income, and consumption per capita. Small-scale irrigation has a larger effect on agricultural production and agricultural income than large-scale irrigation, but large-scale irrigation has a larger effect on consumption per capita. This suggests that market integration and nonfarm externalities are important in realizing gains in agricultural surplus from irrigation.